One Life/Many Lives: An Internal Hindu-Christian Dialogue - Long, Jeffery D. (Religions, 2018)
This essay consists of philosophical and comparative theological reflections on the topic of rebirth, or reincarnation. Informed by the work of William James, John Hick, and Francis X. ClOoney, the essay first establishes the author's stance that reincarnation is a plausible option for belief, at least as attractive as its two main rivals. These rival options are the belief in an everlasting life in either heaven or hell, characteristic of religions such as Christianity and Islam, and the materialist or physicalist belief that there is no afterlife, except in a highly attenuated sense. The essay then moves into a dialogical, comparative theological mode. It raises the question of whether traditional Christian rejection of rebirth, even if it is not something to which the author ultimately assents, might nevertheless carry with it an important insight that is worthy of serious consideration by those who accept the idea of rebirth. This is seen as an instance of the deep learning across religious borders' that is the main goal of comparative theology, as defined by ClOoney.